GATE Civil Engineering
0 votes

If $\text{k}$ is a constant, the general solution of $\dfrac{dy}{dx}-\dfrac{y}{x}=1$ will be in the form of

  1. $y=x\text{ ln}(kx)$
  2. $y=k\text{ ln}(kx)$
  3. $y=x\text{ ln}(x)$
  4. $y=xk\text{ ln}(k)$
in Ordinary Differential Equation (ODE) by (5.2k points)
recategorized by

Please log in or register to answer this question.

Welcome to GATE Civil Q&A, where you can ask questions and receive answers from other members of the community.
Top Users May 2021
  1. Don6

    20 Points

1,173 questions
139 answers
44,308 users